PENERAPAN MODEL INKUIRI TERBIMBING DALAM PEMBELAJARAN MENULIS LAPORAN - Abdu Rozak; - jaja; - Rudianto (Jurnal Tuturan, 2015)
Learning Bahasa Indonesia is deemed to disregard the students’ characteristics including the level of maturity and thinking capability. An appropriate teaching model for grade eight students of junior high school is assumed not the one that releases students to be really independent (free inquiry) rather than the one which is guided (guided inquiry). This needs investigation and this study tries to do so. The main objective of this study is to investigate whether there is significant difference in the writing ability between the students who were subjected to guided inquiry learning model as an experimental group and the students who were grouped in free inquiry learning model. The procedures of guided inquiry are similar to those of free inquiry:  problem identification, data collection, data analysis and conclusions/ making a product. The difference is that guided inquiry emphasize more on the guidance. The guidance is in the form of worksheets that facilitate students to learn. The research was conducted on grade eight of junior high school students in SMP 1 Tengah Tani, Cirebon. To determine the students’ ability in writing reports, a pre-and post-tests were conducted to both control and experimental groups. In addition, an observation was also carried out when treatments were being implemented. Based on t-test statistical analysis on final test scores, there was a significant difference between students’ writing ability in experimental and control groups. The value of t-observe is less than t-table, in probability level 0.05 (p <0.05). This means that the students who learned writing report through guided inquiry model out performed those who learned through (free) inquiry model. The procedures of guided inquiry model are basically inquiry model, but in the learning process, the students should be guided by the teacher. The guidance can be in form of students’ worksheet:  challenge activity. With this worksheet, students were observed to be more independence, though not many discoveries were made. Many student compositions were found to have inappropriate development from writing outline to be a composition and ingrammatical sentences. While linguistic errors lied on spelling, word arrangement and capitalization. Therefore, teaching Bahasa Indonesia should be cautious on the selection of appropriate models. And, the teachers should keep in mind to teach the language aspects as well.